Economic and environmental impact of drone technology in Indian agriculture: An overview - Rahul, D; Varadha, R S; Prahadeeswaran, M; Ragunath, K; Shanmugam, P S; Pangayar, S R; Rajkumar, R; Sarita, J (Plant Science Today, 2025)
Drones or small unmanned aerial vehicles, present a variety of opportunities for the agricultural industry. Drones are widely utilized for real-time airborne photography, sensor data collecting, pesticide spraying, soil analysis and fertilisation and animal monitoring in agriculture. Drones for agricultural spraying are being actively promoted by the Indian federal government. The main goals of these "Kisan drones" are to reduce spraying times, improve the effectiveness and efficiency of using resources for agricultural applications (pesticides, etc.) and lessen the negative health impacts of manually applying pesticides. Drones are anticipated to have a future role in aerial imaging, surveying and transportation in farming. This study shows that the state is actively promoting a more liberalized drone-friendly policy and offering large financial incentives to businesses, groups and specific farmers to buy, use or manufacture drones as needed. In addition to saving time, drones are said to use resources efficiently, saving a significant amount of water. The cost-per-acre unit economics of drone spraying is beginning to catch up with that of manual labour and it reduces input costs by 18 %-20 % and increases crop yields by 30 %-100 % through precision farming. Drones also cut labour and operational costs while enabling efficient coverage of large areas quickly. Environmentally, they lower chemical usage by up to 50 %, conserve water by up to 90 % and reduce the carbon footprint by 25 %. Additionally, drones help reduce post-harvest losses by 50 % and support job creation, making them a key tool for sustainable and productive farming in India.